2007
DOI: 10.1103/physrevlett.99.135502
|View full text |Cite
|
Sign up to set email alerts
|

Anelastic to Plastic Transition in Metallic Glass-Forming Liquids

Abstract: The configurational properties associated with the transition from anelasticity to plasticity in a transiently deforming metallic glass-forming liquid are studied. The data reveal that the underlying transition kinetics for flow can be separated into reversible and irreversible configurational hopping across the liquid energy landscape, identified with and relaxation processes, respectively. A critical stress characterizing the transition is recognized as an effective Eshelby ''backstress,'' revealing a link b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
172
1
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(191 citation statements)
references
References 21 publications
8
172
1
10
Order By: Relevance
“…For example, materials are typically deemed reversible in the regime where the stress-strain curve is linear, and irreversible in the regime where plastic flow occurs [48]. Reversibility has been studied experimentally using enthalpy [18] and strain recovery [19], elastostatic compression [16], nanoindentation [10], and quality factor measurements [49]. In simulations, reversibility has been studied using cyclic shear of model glasses [17,[50][51][52][53][54].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, materials are typically deemed reversible in the regime where the stress-strain curve is linear, and irreversible in the regime where plastic flow occurs [48]. Reversibility has been studied experimentally using enthalpy [18] and strain recovery [19], elastostatic compression [16], nanoindentation [10], and quality factor measurements [49]. In simulations, reversibility has been studied using cyclic shear of model glasses [17,[50][51][52][53][54].…”
Section: Resultsmentioning
confidence: 99%
“…near γ ∼ 0.05), the shear stress reaches a peak (whose height depends on the thermal history, as shown in Fig. 1 (c)) and then begins to decrease until it plateaus at a steady state value in the plastic flow regime [2,18]. (For this system, we employed periodic boundary conditions that prevent fracture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fraction of the flow units is B8% for this specific MG system. Such isolated reversible motions within matrix can be regarded as hopping events across inherent structures and contribute to the brelaxation 26,56 . These few easy flowing spots do not change the brittle nature of MGs.…”
Section: Disscussionmentioning
confidence: 99%
“…Recent studies on the atomic-scale glassy structure have revealed the existence of liquid-like sites in glassy state 4,18,19 , which are presumed to be responsible for the viscoelastic flow behaviour in glasses [20][21][22] . Meanwhile, the studies on glasses have demonstrated that the b-relaxation is identified to play an essential role in the GLT process 2,8,9,11,23 , and the b-relaxation has comparable activation energy with that of the deformation unit and strongly correlated with mechanical brittle-to-ductile transition in MGs 20,21,[24][25][26] , indicating that the b-relaxation is closely related to the initiation and evolution of the localized liquid-like deformation units or flow units in MGs [27][28][29][30] . Yet, the fraction and evolution of these liquid-like zones, leading to the flow phenomena such as elastic and plastic deformations and GLT, are still speculative due to the lack of abundant experimental evidence, and the intrinsic correlations between such deformation transition, relaxation mode and structural characteristics changes during GLT are still poorly understood.…”
mentioning
confidence: 99%